O ensino de botânica numa perspectiva prática, teórica e regional - Lima, Henrique Oliveira (2019)
The Botany has room in classrooms throughout Brazil. The problem is a work carried out, it is the very stimulus of students in learning the plants, as many of them refer as if they are bush, that is, something without much importance. On the other hand, teachers are not motivated to enthusiastically deliver this content. This is a big problem, especially when it comes to an Amazonian language, which is a big problem, which is a being studied, and for that it needs to be preserved. For evaluation, it should be like guidelines for National Curricular Parameters of Natural Sciences and the Common Curriculum, for those documents that the school levels are able to know and understand, for which they are natural to be sustainable. As a way to contribute to the elementary school Rilton Leal Filho, located in Armando Mendes. The research was qualitative and based on action research, which is summarized in a methodological proposal regarding the theme as the participants of the research work together to solve a problem. Thus we proposed the use of plants as a way to release and learn from students by students. For an intervention, to relate as plants with the construction of a didactic sequence based on Zabala, (1998) and Miquelante et al (2017), containing 8 steps, all the different strategies of action (Based on Krasilchik 2008), each with a common element, like medicinal plants. As a way to subsidize the construction of a sequence, we generate a model of information and strategies to draw. This tool was based on Lakatos and Marconi (2010). We also intend to investigate the history of botanical education throughout elementary school as a way to obtain more information for the construction of the sequence. During the sequence, we cover several botanical topics such as: morphology, anatomy, physiology and botanical ecology. In all these, the students had an active participation, and the researcher only assisted when necessary. Finally, by obtaining all the results, we verified that the students learned the proposed subjects, and consequently created an environmental awareness, that led to the reflection on the importance of the conservation of the plants. In the end, we built a didactic product so that other professionals and admirers of the area can use to apply and transform their reality and that of their students, because the vegetal resources need to be understood so that the construction of a sustainable thought and a change of attitude.